On a Dirac type quantization algorithm for the Neumann - Bogoliubov oscillatory dynamical system (Neliniini Kolyvannya, 2001)
A Dirac type quantization algorithm is applied to the Neumann-Bogoliubov oscillatory dynamical system and the corresponding Heisenberg operator equations are derived